Online Forum in Biotechnology Education: A Study from the Students’ Perspective - Wong, Ling Shing; Thong, WengHing (SAVAP International, 2012)
Interaction and communication through online forum is a widespread practice for the university students. To date, many reports indicate positive feedback on the implementation of online forum into the traditional face-to-face teaching and learning process, however the students’ responses on this pedagogical tool in biotechnology education in Malaysia is yet to be reported. The main objective of this study is to learn about the students’ perspective towards the integration of online forum into formal educational process. The feedback from the students were obtained through the questionnaires. The feedback shows only about 5% of the students has experienced taking online forum as formal educational event prior to this study. A total of 56% of the respondents agreed that online discussion had motivated them in their learning process, 61% of them found that the discussion had inspired their creativity, and about 53% of them found that the discussion had increased the interaction between their course mates. On the list of the factors that had motivated them to join the online forum, the students were most concern about the marks carried by joining the forum, closely followed by while the topics which could draw their interest. This study found that online forum is a good tool in teaching biotechnology courses.